2019
DOI: 10.1111/desc.12925
|View full text |Cite
|
Sign up to set email alerts
|

Predicting educational achievement from genomic measures and socioeconomic status

Abstract: The two best predictors of children's educational achievement available from birth are parents’ socioeconomic status (SES) and, recently, children's inherited DNA differences that can be aggregated in genome‐wide polygenic scores (GPS). Here, we chart for the first time the developmental interplay between these two predictors of educational achievement at ages 7, 11, 14 and 16 in a sample of almost 5,000 UK school children. We show that the prediction of educational achievement from both GPS and SES increases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 31 publications
6
46
0
2
Order By: Relevance
“…For the example of reading ability, it has been found that the abilities of both of the parents explain 21% of the ability of children 58 . In comparison, polygenic scores (based on the educational-attainment GWAS) have been found to explain only 2–5% of reading ability in children 59 , and more recently 5–14% of “educational achievement” (including reading, writing, speaking, listening, and mathematics) in ages 7 to 16 years 60 . Certainly this proportion of variance explained from simple polygenic scores is not trivial, and the predictive ability of polygenic scores is anticipated to increase in the coming years.…”
Section: What Researchers Can Domentioning
confidence: 97%
“…For the example of reading ability, it has been found that the abilities of both of the parents explain 21% of the ability of children 58 . In comparison, polygenic scores (based on the educational-attainment GWAS) have been found to explain only 2–5% of reading ability in children 59 , and more recently 5–14% of “educational achievement” (including reading, writing, speaking, listening, and mathematics) in ages 7 to 16 years 60 . Certainly this proportion of variance explained from simple polygenic scores is not trivial, and the predictive ability of polygenic scores is anticipated to increase in the coming years.…”
Section: What Researchers Can Domentioning
confidence: 97%
“…We also found that genetic liability to higher educational attainment, over and above IQ, was associated with lower risk of ADHD. This could be explained in the context of educational attainment being associated with several socio-economic status and lifestyle indicators 41,42 .…”
Section: Bidirectional Causal Associations Between Genetic Liability mentioning
confidence: 99%
“…We focused on within-person grade variability across English, maths, and science, which are the core subjects in compulsory schooling in the UK. We aimed to 1 Previous studies have demonstrated the influence of genetic factors on scholastic success (Kovas et al, 2013;von Stumm et al, 2020), and here we used a twin design to estimate the heritability of within-person grade variability. We also applied a genome-wide polygenic score based on the largest genome-wide association study (GWAS) on educational attainment (Lee et al, 2018) to test the influence of inherited DNA differences on within-person grade variability.…”
Section: The Current Studymentioning
confidence: 99%